Principles of law: Methodological approaches to understanding in the context of modern globalization transformations - Yevhen Leheza; Larysa Nalyvaiko; Oleksandr Sachko; Victor Shcherbyna; Olha Chepik-Trehubenko (Universidad Hemisferios, 2022)
The purpose of the research is to highlight methodological approaches to understanding principles of law in the context of modern globalization transformations. Their ontological, epistemological and axiological nature are revealed, in particular, links of the principles of law with human existence, science and other ways of world perception are being traced. Methodology: The methodological basis of the research is the dialectical method of scientific knowledge, through the application of this method considered were legal, functional, organizational and procedural aspects of methodological approaches to understanding of principles of law in the context of modern globalization transformations. Conclusions. The classification of the principles of law was singled out and a brief description of their types — universal principles, civilizational principles, and right-family principles and possibilities of separating principles of the national legal system was provided. Key words: principles of law, ontological nature, epistemological nature, axiological nature, science, classification, universal principles.